Breast cancer chemoprevention pharmacogenomics: Deep sequencing and functional genomics of the ZNF423 and CTSO genes - Duan Liu (Nature Portfolio, 2017)
Pharmacogenetics: Sequencing finds DNA variants affecting chemoprevention response DNA sequencing has revealed genetic variants that explain inherited variation in responses to preventative drug therapy for breast cancer. Richard Weinshilboum from the Mayo Clinic in Rochester, Minnesota, USA, and colleagues previously showed that genetic variations in or near two genes—ZNF423 and CTSO—affected how well the drugs tamoxifen and raloxifene reduced the rate of breast cancer occurrence. Building on that finding, Weinshilboum’s team has now sequenced these two genes in 199 patients who developed breast cancer during chemopreventative drug therapy and 201 patients who did not. They identified around 4000 single-nucleotide polymorphisms across each gene, 21 of which were close to estrogen response element (ERE) motifs to which ER﻿α﻿ binds. Functional studies pointed to molecular ways in which some of these gene variants alter drug activity.